Vitamin D3 Supplementation as a Potential Therapeutic Strategy to Mitigate Inflammation in Chronic Kidney Disease: An NF-κB-Centric Preclinical Study - Adly; Darmawan Ismail; Kristanto Yuli Yarsa (Open Access Indonesian Journal of Medical Reviews, 2025)
Chronic kidney disease (CKD) represents a global health burden, characterized by progressive loss of kidney function and a heightened state of chronic inflammation. Nuclear Factor-kappa B (NF-κB), a pivotal transcription factor, plays a central role in orchestrating this inflammatory cascade, contributing significantly to CKD progression and associated cardiovascular complications. Vitamin D deficiency is highly prevalent in CKD patients and is increasingly recognized for its potential role in exacerbating inflammation. This preclinical study aimed to investigate the therapeutic potential of Vitamin D3 supplementation in mitigating inflammation by modulating NF-κB levels in an experimental model of CKD. This study employed a post-test only control group design using 24 male albino Rattus norvegicus. CKD was induced, and animals were divided into three groups (n=8 each): a Control group (normal rats), a CKD group (rats with induced CKD receiving no treatment), and a CKD + Vitamin D3 group (CKD rats receiving Vitamin D3 supplementation for four weeks). Blood NF-κB levels were measured weekly for four weeks. Statistical analysis was performed using SPSS, including ANOVA and post-hoc Bonferroni tests, to determine significant differences between groups. NF-κB levels remained stable in the Control group. The CKD group exhibited a significant and progressive increase in blood NF-κB levels over the four-week period (mean at week 4: 657.50 ± 18.68 units/mL). Conversely, the CKD + Vitamin D3 group demonstrated a highly significant and time-dependent reduction in NF-κB levels, decreasing from a mean of 650.72 ± 24.92 units/mL at week 1 to 127.20 ± 4.46 units/mL by week 4 (p < 0.001 compared to the CKD group). Two-way repeated measures ANOVA revealed a significant interaction between treatment and time (p < 0.001). In conclusion, Vitamin D3 supplementation significantly attenuated the rise in blood NF-κB levels in this preclinical model of CKD in Rattus norvegicus. These findings suggest that Vitamin D3 holds promise as a therapeutic strategy to mitigate inflammation in CKD by targeting the NF-κB pathway. Further research is warranted to elucidate the precise molecular mechanisms and to translate these findings into clinical applications for human CKD patients.